KORELASI INFORMASI JENIS PEKERJAAN, STATUS SOSIAL EKONOMI ORANG TUA DAN SARANA PRAKTEK DENGAN MINAT KERJA SISWA KELAS XII PROGRAM KEAHLIAN TEKNIK OTOMOTIF SMK NEGERI 2 BIMA TAHUN AJARAN 2015/2016 - Rizal Ardianto; Slamet Priyanto (Universitas Sarjanawiyata Tamansiswa, 2017)
The aims of this study is to find out; (1) the correlation between the type of job information, socio-economic status of parents and the practice facilities with a working interest (X1); (2) the correlation between the type of job information with the working interest (X2); (3) the correlation between socio-economic status of parents with working interests (X3); and (4) the correlation between practice facilities with a working interest of students of class XII Automotive Engineering Program SMK Negeri 2 Bima 2015/2016 academic year (Y).The research was conducted at SMK Negeri 2 Bima. The research was conducted in the first semester of the 2015/2016 academic year. The population in this study are 127 students taken from all of the students of class XII Automotive Engineering Expertise program. This study used applied try out technique. This research is a Ex Post Facto research. Data collection technique used a questionnaire method. Data analysis techniques used trials using multiple correlation analysis and partial correlation analysis.Based on the data analysis obtained the following results: (1) the results of the analysis of multiple correlation obtained coefficient rhitung 0433 and Fhitung 5629> Ftable 3:32 so it can be concluded that simultaneous correlation exists a positive and significant correlation between information type of work (X1) socioeconomic status (X2) and the practice facilities (X3) with working interests (Y); (2) the results of partial correlation analysis obtained rhitung 0312> rtabel 0176 so it can be concluded that there is a positive and significant correlation between the information type of work with work interests; (3) the results of partial correlation analysis obtained rhitung 0305> rtabel 0176 so it can be concluded that there is a positive and significant correlation between socio-economic status of parents with working interests; and (4) the results of partial correlation analysis obtained rhitung 0.244> 0.176 rtabel so it can be concluded that there is a positive and significant correlation between the practice facilities with a working interest of students of class XII Automotive Engineering Program SMK Negeri 2 Bima the academic year 2015/2016